A Conceptual and Applied Aspect of Ashtavidha Shastra Karma in Shalya Tantra - Gupta, Anshuma; Singh, Sudha (International Research Journal of Ayurveda & Yoga, 2022)
Acharya Sushruta explained the three phases of surgical procedure i.e. Trividh karma which are Poorva karma (preoperative measures), Pradhan karma (operative procedures) and Paschat karma (postoperative measures). The Ashtavidhi shastra karma comes under Pradhan karma which is main operative procedures. Ashtavidha Shastra karmas are the procedures or the steps which are always the soul of any surgery. With a broad vision, Ashtavidha Shastra karmas can be taken as the base of modern surgery and that may be the reason why Acharya Sushruta is still remembered by not only the Ayurvedic but also the modern surgeons. Though, modern surgery is getting improved and updated day by day, still these Shalya Karmas have not lost their shine, because these are the roots of all the surgeries and roots are always more important and essential than the branches.